Strategi Peningkatan Mutu Pembelajaran pada Mata Pelajaran Pendidikan Agama Islam - Khalimi, Khalimi; Nurzaman, Nurzaman (Tsamratul Fikri | Jurnal Studi Islam, 2016)
This research article found some conclusions as follows: (1) strategies for improving the quality of lesson plans on subjects of Islamic Religious Education at SMK Diponegoro is to develop a planning system for effective learning, which is a planning process that can help create the desired results, as well as the process to assign to where to go and how to get there in a way that is most effective and efficient. Planning effective learning must contain (i) the learning objectives to be achieved; (ii) the strategy to achieve the learning objectives; (iii) the resources that can support, including media, learning resources and others; and (iv) implementation planning. (2) improving the quality of the learning process is done with some strategies, namely: (i) develop teaching methods that correspond to the learning objectives that draw on the habituation and exemplary. (ii) use of instructional media that are relevant, easy to use, and affordable. (iii) develop authentic learning evaluation, which is an assessment that refers to the real-world situation or context, sustainable, and individual. (3) strategies to improve the learning outcomes of students are to (i) optimize the implementation of the learning plan, (ii) optimization of the use of learning methods through habituation and exemplary, especially to improve learning outcomes in the realm of affective, psychomotor, and morals learners. (iii) optimize the use of media in accordance with the needs of learners, competencies that must be mastered, learning materials, and the ability of teachers. (iv) the development of motivation, discipline, and interests of learners in the subject of Islamic Education.